Optimization Design And Simulation for Driving Mechanism of Flapping-wing Air Vehicle - Yang Yonggang; Su Hanping (Jixie chuandong)
In allusion to the study of flapping- wing air vehicles（ FAV） with double- crank and double- rocker kind construction at present,the optimization design method of the flapping- wing driving mechanism with maximum value of minimum transmission angle is studied and analyzed. Based on classic graphical method on four- bar linkage mechanism,the function relation model of minimum transmission angle and the length of FAV is established. According to the bionic condition of birds flapping- wing flight,the installation angle and flap- wing flapping range and the function of crank driven angle are introduced. An optimization design scheme of the driving mechanism is obtained by utilizing Matlab. The virtual prototype of flapping- wing driving mechanism is built and a virtual kinetic simulation is conducted by utilizing ADAMS,the result shows that the optimization design model of driving mechanism is conformed with theory parameter model of FAV flapping,thus this design method is proved to be practicable and efficient.